2012
DOI: 10.1080/07373937.2011.620726
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying of Mannitol as a Drug Carrier—The Impact of Process Parameters on Product Properties

Abstract: Powders intended for the use in dry powder inhalers have to fulfill specific product properties, which must be closely controlled in order to ensure reproducible and efficient dosing. Spray drying is an ideal technique for the preparation of such powders for several reasons. The aim of this work was to investigate the influence of spray-drying process parameters on relevant product properties, namely, surface topography, size, breaking strength, and polymorphism of mannitol carrier particles intended for the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 25 publications
0
43
0
1
Order By: Relevance
“…The great advantage of using mannitol in place of a-lactose is the possibility of using spray dryer to design particle without affecting product stability [11]. SDM particle sizes can be modified by changing the droplet size during atomization; the concentration of the feed solution or the solubility of the solute [12].…”
Section: Introductionmentioning
confidence: 99%
“…The great advantage of using mannitol in place of a-lactose is the possibility of using spray dryer to design particle without affecting product stability [11]. SDM particle sizes can be modified by changing the droplet size during atomization; the concentration of the feed solution or the solubility of the solute [12].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Littringer et al found that influence of feed concentration on the droplet size at high atomizer revolution rates is less 48 . This is also an example of possible complex interaction between various process parameters (in this case between feed concentration and atomizer revolution rate).…”
Section: Influence Of Solute Components In Feed Solutionmentioning
confidence: 99%
“…This can affect the morphology of the dried particle. Temperature variation results in different surface properties and shape such as particle roughness 48,54 . Higher inlet temperature results in enlarged particle diameter 51 .…”
Section: Inlet and Outlet Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations